STUDY OF PECTIN CAPABILITY TO ADSORB Cd(II) IN AQUEOUS SOLUTION AND ITS SELECTIVITY WITH Zn MINERAL - Meiliana Meiliana; Mellia Harumi (Soegijapranata Catholic University, 2024)
The polluted environment will lead to food chain contamination and risk to human health. As an eco-friendly adsorbent, pectin has been studied to adsorb Cd(II) and other heavy metal ions effectively. It has the potential to prevent heavy metal ions absorption but might interfere mineral absorption during the digestive process. This research aimed to analyze the ability of pectin to adsorb Cd(II) ions in multi metal solutions at stomach condition (pH 2) and small intestine condition (pH 6) with competition to other mineral Zn as essential nutrient. About 0.2 grams of pectin was dispersed into multi metal solution 32 ppm of Cd(II) and 1 ppm of Zn(II) in pH 2 and 6. Metal ions were analyzed using Atomic Absorption Spectroscopy (AAS). The result proved that pectin can adsorb 0.32 ppm (29.03%) of Zn(II) and 13.8 ppm (38.87%) of Cd in pH 2. Pectin was more selective to adsorb Zn(II) in pH 6 where minerals were absorbed. This analogue result also provided distribution coefficient (D) which lead to the increasing of pectin selectivity towards Zn(II) with increasing of pH. The very high performance of pectin was selective for Cd in pH 2 αCd/Zn of 1.55.